“It Is Not Me Who Is the Host, But Nature Itself”. An Ecocentric Analysis of the Creative Legacy of Vasyl′ Tkachuk - Horniatko-Szumiłowicz, Anna (Poznańskie Studia Slawistyczne, 2022)
The interpretation of Vasyl′ Tkachuk’s stories from an ecocritical point of view showcases new aspects of understanding the prose legacy of this remarkable writer. Of course, the true love for the Hutsul region, one that the “proud” Hutsul people live in harmony with, one that, unlike in the works of Vasyl′ Stefanyk, is not only the cause of the Hutsul people’s extreme poverty but is sincerely loved and praised by them, is not the only merit of Tkachuk’s stories. Ecocritical dimensions of the “humble rural pictures, so touching to the core” ( Mykhaylo Rudnytskyi ) imply certain aspects of the critical literary analysis of Tkachuk’snovels, such as ethno national identity of the author and his characters, unbreakable unitywith the traditions of ancestors, apotheosis of the soil—one that not only feeds but is also responsible for the unique “national spirit” of the Carpathian highlanders, ecological awareness of the old Hutsul people and the philosophical layer of the literary legacy of the author.